2005
DOI: 10.1115/1.2170129
|View full text |Cite
|
Sign up to set email alerts
|

Power Assessment of Flowing Compressed Air

Abstract: This study proposes a new concept for quantifying the energy of flowing compressed air, called air power. Air power is defined as the work-producing potential of compressed air, and its definition and general equation are presented. The properties of air power are also discussed. Air power is comprised of two components, transmission power and expansion power, while air temperature and kinetic energy can generally be neglected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(69 citation statements)
references
References 1 publication
0
69
0
Order By: Relevance
“…Here, R is the universal gas constant (8.314 J/mol K), T is the gas temperature (298 K), and is the molecular weight of CO 2 (0.044 kg/ mol). The energy consumed per cycle (E c ) was calculated from E c = P 1 V 1 1n P 1 /P a [22]. Additionally, we calculated the initial stored energy of the bottle (E b ) using the equation E b = m/μ RT 1n P 1 /P a , where m is the mass of CO 2 in the bottle (0.255 kg).…”
Section: Empirical Characterization Of Ppafo System Performancementioning
confidence: 99%
“…Here, R is the universal gas constant (8.314 J/mol K), T is the gas temperature (298 K), and is the molecular weight of CO 2 (0.044 kg/ mol). The energy consumed per cycle (E c ) was calculated from E c = P 1 V 1 1n P 1 /P a [22]. Additionally, we calculated the initial stored energy of the bottle (E b ) using the equation E b = m/μ RT 1n P 1 /P a , where m is the mass of CO 2 in the bottle (0.255 kg).…”
Section: Empirical Characterization Of Ppafo System Performancementioning
confidence: 99%
“…To monitor these systems, flow measurements are required [1][2][3][4]. In order to detect and quantify gas flow rates, non-invasive measurement techniques whose sensors are installed outside the gas pipelines and indirectly contact with gases are recommended, as these techniques have an evident advantage that it is not necessary to break pipelines to install sensors when measuring.…”
Section: Introductionmentioning
confidence: 99%
“…Cai et al [3,4] have shown that CA power (exergy rate) has two parts: (a) the transmission power used for pushing CA towards to the application side and (b) the expansion power, which can be used when CA is expanding after closing inlet valve. Although the latter represents the larger part of all CA powers above This energy is wasted during retract motion of the cylinder as CA is ventilated to the atmosphere.…”
Section: Application Sidementioning
confidence: 99%
“…The exergy represents the amount of useful energy, which can be theoretically converted to mechanical energy. It can be easily shown that in the case of CAS, only the pressure-dependent term is critical [3,4]. Equation (1) shows the mathematical formulation of exergy referenced to the ambient conditions (subscript a) based on ideal gas approach.…”
Section: Exergy Definitionmentioning
confidence: 99%
See 1 more Smart Citation